2024
DOI: 10.4240/wjgs.v16.i3.700
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the impact of immunotherapy efficacy and safety in patients with gastric cancer and liver metastasis

Kai Liu,
Chun-Xiao Wu,
Hui Liang
et al.

Abstract: BACKGROUND Gastric cancer (GC) is the fifth most common type of cancer and has the fourth highest death rate among all cancers. There is a lack of studies examining the impact of liver metastases on the effectiveness of immunotherapy in individuals diagnosed with GC. AIM To investigate the influence of liver metastases on the effectiveness and safety of immunotherapy in patients with advanced GC. METHODS This retrospective investigation collected clinical data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
(24 reference statements)
0
4
0
Order By: Relevance
“…In research of renal cell carcinoma and melanoma, Kaplan-Meier analysis also presented longer OS and PFS in non-LM patients receiving systemic therapy[ 8 , 9 ]. In the latest issue of the World Journal of Gastrointestinal Surgery , Liu et al [ 10 ] found that immunotherapy was less effective in patients with advanced gastric cancer and LM, which expanded the findings to gastric cancer.…”
Section: Lm Restrains Efficacy Of Immunotherapymentioning
confidence: 99%
“…In research of renal cell carcinoma and melanoma, Kaplan-Meier analysis also presented longer OS and PFS in non-LM patients receiving systemic therapy[ 8 , 9 ]. In the latest issue of the World Journal of Gastrointestinal Surgery , Liu et al [ 10 ] found that immunotherapy was less effective in patients with advanced gastric cancer and LM, which expanded the findings to gastric cancer.…”
Section: Lm Restrains Efficacy Of Immunotherapymentioning
confidence: 99%
“…Another problem that may make immunotherapy impossible or reduce its effectiveness is the stage of advancement and the presence of GC metastases. Interestingly, Liu et al [ 20 ] showed that immunotherapy is less effective in patients with GC with liver metastases compared with those without liver metastasis.…”
Section: Immunotherapy In Gastric Cancermentioning
confidence: 99%
“…Interactions between immune checkpoint molecules PD-1 or CTLA-4 and their receptors on immune system cells are presented in Figure 2. [20] showed that immunotherapy is less effective in patients with GC with liver metastases compared with those without liver metastasis.…”
Section: Immune Checkpoint Moleculesmentioning
confidence: 99%
“…Digestive system tumors, including colorectal cancer (HR: 1.35, 95%CI: 1.07-1.71) and gastric/esophagogastric cancer (HR: 1.17, 95%CI: 0.90-1.52), were less affected. In a retrospective study by Liu et al [ 17 ], which is the focus of this editorial, 48 patients were included, 20 of whom had liver metastases. The objective response rates were 15.0% and 35.7% in the metastatic and nonmetastatic cohorts, respectively ( P > 0.05).…”
Section: Introductionmentioning
confidence: 99%